Modelica-based multiphysics modeling and multi-timescale dynamic analysis of a 100-kW alkaline water electrolysis system - Yin, Ruilin; Chen, Bin; Sun, Li (Renewable energy, 2025)
Alkaline water electrolysis is a promising technology to meet the large-scale and long-term energy storage demands of renewable energy resources (RESs). However, the electrolysis system is faced with varying loads due to the non-dispatchable renewable power input. To facilitate efficient transient operation and provide insights into electrochemical, thermochemical, fluidic, and gaseous domains, a multiphysics analytical model is developed for the analysis of the electrolysis system. A one-dimensional electrolyzer and the balance of pant system models such as heat exchangers, gas separators, pumps and compressors are developed using an object-oriented language Modelica. The developed models are then utilized for numerical studies and thermodynamic analysis with both steady-state and dynamic simulations. Sensitivity analysis is studied to reveal the parameters’ distribution characteristics. The steady-state analysis results show a large lye flow rate uniform the temperature distribution while enlarge the gas impurity. Considering the volume inertia and heat capacity of the system, a dynamic analysis is carried out through multiphysics including electrochemical, fluidic, gaseous and thermochemical domains. The results show heat capacity and volumetric inertia have a major influence on the response time of temperature and gas production. The research in this paper provides a reference of response characteristics for the subsequent control design.